Shared financial management of Community programs and its implementation in the EU area - Jedličková, Vladislava; Heřman, Jan; Dvořáček, Jiří, 1947-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The issue of migration within the European Union has grown in member countries to considerable size. Management representatives of EU institutions have decided to address this situation. They established community program Solidarity and management of migration flows. The European Commission has decided that for the financial management of this program will be used the principle of shared management. The principle of shared financial management is the delegation of powers and responsibilities for funding and implementing the program from the institutions of the European Commission to the Member State. This decision creates an obligation for a Member State to establish a system of financial management programs in accordance with financial rules of the European Union (not by the financial rules of the Member State). So the general program "Solidarity and management of migration flows" became the first community program in the CR, which is being implemented on the principle of shared financial management. Member states are obliged to create their own theoretical and methodological basis of a new financial management. This method of financial management has three pillars - Responsible Authority, Audit Authority and Certification Authority. The recipient of funds may be non-profit organizations or state or public nonprofit organization. The financial management of the Responsible Authority is responsible for program implementation in the Member State through projects of final beneficiaries. The Audit Authority is the control body. The Certification Authority is the authority for confirmation. It is the last link between the European Commission and Member States. The task of the Certification Authority and at the same time of this dissertation was to develop new theoretical and methodological system of internationally recognized certification of public expenditures for services that are financed from the EU budget.
In the past, the issue of certification of the expenditures financed by community programs in the CR was not addressed. The goal set in my work was met. New theoretical and methodological certification system was created. Functionality and effectiveness of the system was checked before being put into practice through expert assessment by experts of the Ministry of Interior and Ministry of Finance. Also theoretical and methodological approach was developed, which was approved by the Minister of the Interior, and which became a mandatory certification standard for all involved organizations in the CR. The system was put into practice and has been used since 2009.
Vedoucí práce: Jan Heřman
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations